The Television Industry as a Market of Attention - Nilssen Tore (Nordicom Review, 2010)
In this article, I present an economist’s perspective on the TV industry and view it as a so-called two-sided market, with advertisers on the one side benefiting from the presence of TV viewers and TV viewers on the other side having a dislike for advertising on TV. I use this framework to discuss the likely future development of pay TV, in particular how a future increase in competition in the TV industry will affect the prevalence of pay TV over advertising-financed TV.